Laparoscopic single port radical prostatectomy in the 2020: Why not? Our experience. Issue 3 (August 2021) - Sortino, Giuseppe; Giannubilo, Willy; Di Biase, Manuel; Marconi, Andrea; Diambrini, Maurizio; Ferrara, Vincenzo
Objectives: To analyze the feasibility, safety and advantages of Laparo-Endoscopic Single-site Surgery radical prostatectomy (LESS-RP) based on our personal experience. Patients and methods: Details of 520 patients were retrospectively analyzed, from 2009 to 2019. Extraperitoneal approach, with only two accesses (2.5 cm and 5 mm respectively) was used to perform radical prostatectomy. Perioperative characteristics and postoperative oncologic and functional outcomes are reported. Results: The mean age was 66.6 ± 5.6 years. Mean PSA level was 9 ± 3.5 ng/ml. According to D'Amico classification, the percentage of patients with low-, intermediate-, and high-risk disease cases were 116 (22.4%), 275 (52.8%), and 129 (24.8%) respectively. Mean operative time was 156 ± 43 min. Mean estimated blood loss was 214 ± 93 ml. Positive surgical margins (PSMs) were detected in 110 (21.2%) patients. PSM rates in pT2 and pT3 stages were 20.1% and 22.9%, respectively. The overall complication rate was 9.2%, based on the modified Clavien classification. The 12 months continence and potency rates were 90.9% and 49.1%, respectively. The biochemical recurrence rate was 6.8%, at the median follow-up time of 26.7 months (IQR 12–32). Conclusions: Our analyses show that LESS-RP is a safe procedure, if performed by surgeons with adequate experience and skills. Unlike the classic laparoscopic prostatectomy, this technique allows better aesthetic and psychological results, reduced postoperative pain, and a faster return to normal daily activity with the same functional and oncological results.